Pharmacist joint-working with general practices: evaluating the Sheffield Primary Care Pharmacy Programme. A mixed-methods study. Issue 4 (2018) - Marques, Iuri; Gray, Nicola Jane; Tsoneva, Jo; Magirr, Peter; Blenkinsopp, Alison
No abstract available